2021
DOI: 10.1038/s41467-021-25078-5
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory impact of RNA-binding proteins on microRNA targeting

Abstract: Argonaute is the primary mediator of metazoan miRNA targeting (MT). Among the currently identified >1,500 human RNA-binding proteins (RBPs), there are only a handful of RBPs known to enhance MT and several others reported to suppress MT, leaving the global impact of RBPs on MT elusive. In this study, we have systematically analyzed transcriptome-wide binding sites for 150 human RBPs and evaluated the quantitative effect of individual RBPs on MT efficacy. In contrast to previous studies, we show that most RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 62 publications
2
42
0
Order By: Relevance
“…For two of the four modes in the model, methylation facilitated target binding by miRNAs. In another recent study with a focus on RBPs and miRNA targeting, most RBPs were found to enhance miRNA targeting by increasing target site accessibility ( Kim et al , 2021 ). For miRNA targeting, the importance of target structure and binding site accessibility was established over 14 years ago ( Long et al , 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…For two of the four modes in the model, methylation facilitated target binding by miRNAs. In another recent study with a focus on RBPs and miRNA targeting, most RBPs were found to enhance miRNA targeting by increasing target site accessibility ( Kim et al , 2021 ). For miRNA targeting, the importance of target structure and binding site accessibility was established over 14 years ago ( Long et al , 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…It appears that some effects of these miRNAs are cell type specific. miRNA-mRNA binding in cells is influenced by other regulatory factors (RNA binding Proteins, miRNA sponges) causing such differences in miRNA-mRNA interaction in various cell lines [ 47 49 ]. The effect of miR-24 on STING signaling is independent of cGAS, as experiments with STING agonist cGAMP also depicted the regulatory role of miR-24 on STING signaling ( S1B Fig ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intergenic regions that are involved in the process of non-coding RNA biogenesis are also enriched for CELF proteins [7,8,12]. RBPs have recently been found to improve miRNA targeting (MT) by opening mRNA secondary structures [2]. Notably, the "UU-UGUUU" motifs, which are similar to CELF binding sites, are enriched adjacent to miRNA binding sites, and their presence tends to potentiate miRNA activity [150].…”
Section: Noncoding Rna Regulation By Celfmentioning
confidence: 99%
“…According to a new discovery, the RNA structure becomes more open as the number of bound RBPs rises. When the RNA becomes less organized, miRNAbound AGO may easily reach the MT sites by replacing the RBPs that were previously bound, resulting in productive MT [2]. However, to address the complex relation between RBPs and noncoding RNA production more conclusively, future efforts should be made to generate and analyze large-scale transcriptomic and proteomics datasets.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation